LOS VERTEBRADOS DEL PLEISTOCENO TARDIO-HOLOCENO DEL ARROYO NAPOSTA GRANDE, PROVINCIA DE BUENOS AIRES: ASPECTOS PALEOAMBIENTALES (Ameghiniana, 2013)
Late Pleistocene-Holocene vertebrates found in the Arroyo Napostá Grande Banks, Buenos Aires province, are studied. The late Pleistocene fauna from the Middle Member of Agua